Preventing Substance Use Among Indigenous Adolescents in the USA, Canada, Australia and New Zealand: a Systematic Review of the Literature - Snijder, Mieke (Prev Sci, 2019)
This systematic review assessed the current evidence base of substance use prevention programs for Indigenous adolescents in the USA, Canada, Australia and New Zealand. The authors investigated (a) the outcomes, type, setting and context of prevention programs; (b) the common components of beneficial prevention programs; and (c) the methodological quality of evaluations of included prevention programs. The authors searched eight peer-reviewed and 20 grey literature databases for studies published between 1 January 1990 and 31 August 2017. Data extracted included type of program (culturally adapted, culture-based or unadapted), the setting (school, community, family or multi-setting), delivery (computerised or traditional), context (Indigenous-specific or multi-cultural environment) and common components of the programs. Program evaluation methodologies were critically appraised against standardised criteria. This review identified 26 eligible studies. Substance use prevention programs for Indigenous youth led to reductions in substance use frequency and intention to use; improvements in substance-related knowledge, attitudes and resistance strategies; and delay in substance use initiation. Key elements of beneficial programs included substance use education, skills development, cultural knowledge enhancement and community involvement in program development. Five programs were rated as methodologically strong, seven were moderate and fourteen were weak. Prevention programs have the potential to reduce substance use among Indigenous adolescents, especially when they are developed in partnership with Indigenous people. However, more rigorously conducted evaluation trials are required to strengthen the evidence base.